Credit Purchase Decision at PT. Finansia Multi Finance Bangkinang Based on Quality of Service and Trust - Librina Tria Putri; Absor Marantika; Adi Setiawan; Muhammad Salis; Royansyah Putra; Novia Rahma Diani (Greenation Research & Yayasan Global Resarch National, 2023)
This study aims to determine the purchase decision on credit at PT. Finansia Multi Finance Bangkinang which is influenced by service quality and trust partially and simultaneously. The data used in this study are primary data and secondary data, which were obtained using questionnaires, file research, and interviews. The sample used to test the hypothesis is 90 people, namely consumers who use a credit payment system at PT. Finansia Multi Finance Bangkinang using the slovin formula. The data analysis technique used is multiple linear regression analysis with hypothesis testing carried out by the F test and t test at an alpha of five percent. Based on the results of the study it was concluded that the variables of service quality and trust have a significant effect simultaneously and partially on purchasing decisions. The correlation coefficient (R) was obtained for 0.836, meaning that there is a close relationship between the variables of service quality and trust with purchasing decisions. Furthermore, the contribution of service quality and trust variables to purchasing decisions is 77.2% while the remaining 22.8% is influenced by other factors outside the model.